Intelligent Systems and Applications Proceedings of the 2022 Intelligent Systems Conference (IntelliSys) Volume 3 - Arai, Kohei (Lecture Notes in Networks and Systems, 2023)
XII, 847 p. 398 illus., 284 illus. in color.